Construcción de la curva de estado evolutivo de sigatoka negra (mycosphaerella fijiensis morelet.) en banano orgánico. - Rodriguez Cabrera, Alex Alexander (Machala : Universidad Técnica de Machala, 2020)
The banana is a crop that originates from Southeast Asia, it develops in underwood conditions. The main producing countries are India, China, Indonesia, Brazil, Ecuador, the Philippines, Guatemala and Colombia. Exports are distributed among the regions of Latin America and the Caribbean, Asia and Africa. In 2019, approximately 20.2 million tons were exported. Imports are led by the European Union with 31% of total annual imports, followed by the United States with 22%, China with 12%, the Russian Federation with 7.8%, Japan with 5.4% and finally Latin America and the Caribbean with 4.5%. Bananas are one of the main essential crops in Ecuador's economy, generating jobs for various families. In Ecuador, approximately 180,336.00 hectares are cultivated, which has the best soil and climate conditions for the production, which is why the Ecuadorian banana is considered the best in the world for the quality of the fruit. The largest production of bananas in the country is located in the province of El Oro, Guayas and Los Rios. The organic banana is an innovative production that allows to eliminate the use of agrochemicals and to reduce the environmental contamination, being one of the most quoted bananas in other countries because of the nutritional benefits that it contributes to our health. The province of El Oro is the main producer of organic bananas in the world due to the quality of the product and the soil and climatic conditions of the site. The main problem in the production of organic bananas is black sigatoka and its control, therefore, this research topic is formulated to know management alternatives, whose general objective is to construct the curve of the evolutionary state of black sigatoka in organic bananas based on the degree of contamination. The research was conducted at the farm "Santa Inés" located in the parish of El Cambio, province of El Oro. In order to make the biological pre-warning, 30 young plants were chosen from the organic banana staff, they were divided into groups of 10 plants to have an adequate record of the evolutionary state of black sigatoka in a calendar year, the control was made weekly. The following variables were studied: Relative humidity (%), Precipitation (mm), Past leaf emission (EFP), Current leaf emission (EFA), Leaf emission rate (REF), Candle correction (CC), Evolution coefficient (CE), Gross sum (SB), Evolution sum (SEV) and Evolutionary state (EE). The results reflect that there are differences between the first and last months of the year, it is noted that soil and climatic conditions, phytosanitary control and cultural practices directly influence the evolution of the pathogen, as shown in the month of October with an average of 2168.65 has the highest evolutionary state with a tendency to be higher, while September with an average of 1808.77 is the best month for efficiently perform the phytosanitary practices necessary for the control of sigatoka. It is concluded that the cultural practices in the banana plants reduce the level of contamination, allowing the producer to have the adequate conditions for the production of the crop.
El banano es un cultivo originario del sureste asiático, se desarrolla en condiciones de sotobosque. Los principales países productores son la India, China, Indonesia, Brasil, Ecuador, Filipinas, Guatemala y Colombia. Las exportaciones están distribuidas entre las regiones de América latina y el caribe, Asia y África. En 2019 se exportaron aproximadamente 20,2 millones de toneladas. Las importaciones están encabezadas por la Unión Europea con 31% del total de importaciones anuales, seguido de Estados Unidos con 22%, China con 12%, Federación Rusa con 7,8%, Japón con 5.4% y por último América Latina y el Caribe con 4.5%. El banano forma parte de uno de los principales cultivos esenciales en la economía del Ecuador, generando empleos para diversas familias. En Ecuador se cultivan aproximadamente 180,336.00 de hectáreas, que tiene las mejores condiciones edafoclimáticas para la producción, por lo cual el banano ecuatoriano es considerado el mejor del mundo por la calidad de la fruta. La mayor producción de banano en el país está situada en la provincia de El Oro, Guayas y Los Ríos. El banano orgánico trata de una producción innovadora que permite eliminar el uso de agroquímicos y reducir la contaminación ambiental, siendo uno de los bananos más cotizados en otros países por los beneficios nutricionales que aporta a nuestra salud. La provincia de el Oro es la principal productora de banano orgánico del mundo por la calidad del producto y las condiciones edafoclimáticas del sitio. El principal problema en la producción de banano orgánico es la sigatoka negra y su control, por lo tanto, se formula este tema de investigación para conocer alternativas de manejo, cuyo objetivo general es construir la curva del estado evolutivo de la sigatoka negra en banano orgánico en base al grado de contaminación. La investigación se realizó en la granja “Santa Inés” situada en la parroquia el Cambio, provincia de el Oro. Para realizar el preaviso biológico se escogieron 30 plantas jóvenes de la plantilla de banano orgánico, se dividieron en grupos de 10 plantas para tener un adecuado registro del estado evolutivo de la sigatoka negra en un año calendario, el control se lo realizaba semanalmente. Se estudiaron las siguientes variables: Humedad relativa (%), Precipitación (mm), Emisión foliar pasada (EFP), Emisión foliar actual (EFA), Ritmo de emisión foliar (REF), Corrección de candela (CC), Coeficiente de evolución (CE), Suma bruta (SB), Suma de evolución (SEV) y Estado evolutivo (EE). Los resultados reflejan que existen diferencias entre los primeros y últimos meses del año, se señala que las condiciones edafoclimáticas, control fitosanitario y prácticas culturales influyen directamente en la evolución del patógeno, como se muestra en el mes octubre con una media de 2168.65 tiene el estado evolutivo más elevado con tendencia a ser mayor, mientras que septiembre con una media de 1808.77 es el mejor mes por efectuar con eficiencia las practicas fitosanitarias necesarias para el control de la sigatoka. Se concluye que las prácticas culturales en las plantas de banano reducen el nivel de contaminación, permitiendo al productor tener las condiciones adecuadas para la producción del cultivo.
Keywords: PRODUCCIÓN; EVOLUTIVO; PREAVISO; BIOLÓGICO